2017
DOI: 10.1097/md.0000000000008713
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pentax AirwayScope and McGrath MAC videolaryngoscope for endotracheal intubation in patients with a normal airway

Abstract: Various videolaryngoscopes (VLs) have been developed to provide a better laryngeal view and facilitate difficult intubations. The goal of this study was to compare 2 VLs, the Pentax AWS and the McGrath VL, with respect to intubation time and ease of intubation.One hundred forty patients aged 19 to 65 years (American Society of Anesthesiologists classification I or II), who required tracheal intubation for elective surgery, were randomly assigned to 1 of the 2 groups: the Pentax AWS (n = 70) or the McGrath VL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
(51 reference statements)
0
12
0
1
Order By: Relevance
“…In a previous study comparing MVL and PVL during orotracheal intubation, although PVL provided superior glottic view over MVL, the TTI and ease of intubation were similar between the two devices. 25 Second, it may be difficult to direct the tube tip into the glottis. PVL is designed for orotracheal intubation, while the ETT is inserted into the channel during intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study comparing MVL and PVL during orotracheal intubation, although PVL provided superior glottic view over MVL, the TTI and ease of intubation were similar between the two devices. 25 Second, it may be difficult to direct the tube tip into the glottis. PVL is designed for orotracheal intubation, while the ETT is inserted into the channel during intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The physicians' familiarity with MVL might have reduced the intubation times, especially in patients with MILS that simulated difficult airway conditions. Since experienced anesthetists were able to achieve similar intubation times and ease of intubations with PVL and MVL in patients with normal airways, 25 further studies about the experience of intubation with VLs are needed. Third, the blade tip of PVL was positioned behind the epiglottis for direct elevation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsunclassified
“…We based our sample size according to Yumul et al [12]. They used the McGrath MAC in morbidly obese patients and they found the total intubation time to be 62 ± 31 s. Lee et al [13] used the McGrath MAC in normal patients and found the total intubation time of nonobese patients to be 32 (27)(28)(29)(30)(31)(32)(33)(34)(35) s. Based on this data, for a = 0.05 and b = 0.2 we calculated our sample size as 40 patients in each group. Continuous data were examined for normal distribution with the Kolmogorov-Smirnov test.…”
Section: Total Orotracheal Intubation Timementioning
confidence: 99%